Sphingosine 1-phosphate signaling pathway in inner ear biology. New therapeutic strategies for hearing loss? - Romero-Guevara, Ricardo; Cencetti, Francesca; Donati, Chiara; Bruni, Paola (Frontiers in Aging Neuroscience, 2015)
Hearing loss is one of the most prevalent conditions around the world, in particular among people over 60 years old. Thus, an increase of this affection is predicted as result of the aging process in our population. In this context, it is important to further explore the function of molecular targets involved in the biology of inner ear sensory cells to better individuate new candidates for therapeutic application. One of the main causes of deafness resides into the premature death of hair cells and auditory neurons. In this regard, neurotrophins and growth factors such as insulin like growth factor are known to be beneficial by favouring the survival of these cells. An elevated number of published data in the last twenty years have individuated sphingolipids not only as structural components of biological membranes but also as critical regulators of key biological processes, including cell survival. Ceramide, formed by catabolism of sphingomyelin and other complex sphingolipids is a strong inducer of apoptotic pathway, whereas sphingosine 1-phosphate (S1P), generated by cleavage of ceramide to sphingosine and phosphorylation catalysed by two distinct sphingosine kinase enzymes, stimulates cell survival. Interestingly S1P, by acting as intracellular mediator or as ligand of a family of five distinct S1P receptors (S1P1-S1P5), is a very powerful bioactive sphingolipid, capable of triggering also other diverse cellular responses such as cell migration, proliferation and differentiation, and is critically involved in the development and homeostasis of several organs and tissues. Although new interesting data have become available, the information on S1P pathway and other sphingolipids in the biology of the inner ear is limited. Nonetheless, there are several lines of evidence implicating these signalling molecules during neurogenesis in other cell populations. In this review, we discuss the role of S1P during inner ear development, also as guidance for future studies.